Pants-tastic performances. (2nd October 2021) - Harries, Judith
Abstract : Claire Freedman is a highly successful author of many entertaining picture books for young children, featuring pants-obsessed aliens and dinosaurs, best friends Oliver and Patch, and lots of different monsters.